Low Self-Control and Vaping: The Mediating Role of Health and Risk Perceptions. (12th May 2022) - Intravia, Jonathan; Vito, Anthony G.; Rocheleau, Gregory C.
Abstract: Background: Research has shown independent attention in the role of self-control and health/risk perceptions toward vaping in predicting vaping use among youth and young adults. Yet, there are good theoretical notions to believe that low self-control, perceptions toward vaping, and self-reported vaping are intertwined. Objectives: To examine whether three different health/risk perceptions toward vaping mediate the effect of low self-control on vaping use among young adults. Methods: A survey was administered to 325 undergraduate students attending a large university in the Midwest (Mean age = 19.5; 60.4% female; 73.1% White). Single and multiple mediation modeling strategies were used to assess the mediation hypothesis. Results: Logistic regression results indicate that individuals with low self-control are more likely to vape (O.R. = 1.041, p < .05). Further, when health/risk perceptions are included in the models individually and simultaneously, it reduces the effect of low self-control on vaping between 15% and 37.5%, and renders low self-control to become non-significant. Conclusions: Findings suggest the impact that harm/risk perceptions toward vaping have in engaging in this behavior. Thus, preventative efforts should target potential sources, such as media and advertisements, that may shape young adults' perceptions toward vaping.